Since y = 5x-1, we can fill it into 3x + 3y = -3. First, let's look at relating to a simpler equation. Let's say that x + y = 9 and y = 3 + 5. Now, we can fill it in to get that x + (3 + 5) = 9. Now, we know that 3+5 is 8, so x + 8 = 9. Now, x = 1. Likewise, we can do the same. For 3x + 3y = -3, all we need to do is to switch the y in 3x + 3y = -3 with 5x - 1. So it would become 3x + 3(5x - 1) = -3. Now we distribute to get 3x + 15x - 3 = -3. Now add three to both sides to get 3x + 15x = 0. Now simplify to get 18x = 0. Now we know that x = 0. Now fill x into y = 5x - 1. So y = 5(0) - 1. Now we know that y = -1.
To check fill in the answer to 3x + 3y = -3.
3(0) + 3(-1) = -3
0 + (-3) = -3
0 - 3 = -3
-3 = -3
Now that our check is completed we now know that x is 0 and y is -1.
Answer:
For finding the inflection points you'll have to put the first derivative equal to zero and solve for x. After you've done that, you can plug in the x you've just found into the original function and find also the y, so you'll find the ordered pair (x,y) of the inflection point(s).
Answer:
d.
Step-by-step explanation:
Hello!
The population is the set of elements that you are interested in studying. In this example, the instructor wants to know the number of days Lake Tahoe Community College math students are absent from class during a quarter. To do so she will take a random sample of math students and register the number of absences of each student. Each math student is an element of the population.
Then the population is "Lake Tahoe Community College math students"
I hope it helps!
Answer:
A
Step-by-step explanation:
you will get 3(x-1)×(x+1) you can get the 3 and x by itself then it would be x+3